The combined use of tigecycline with high-dose colistin might not be associated with higher survival in critically ill patients with bacteraemia due to carbapenem-resistant Acinetobacter baumannii. (June 2018) - Amat, T.; Gutiérrez-Pizarraya, A.; Machuca, I.; Gracia-Ahufinger, I.; Pérez-Nadales, E.; Torre-Giménez, Á.; Garnacho-Montero, J.; Cisneros, J.M.; Torre-Cisneros, J.
Abstract: Objective: To assess the association of survival and treatment with colistin and tigecycline in critically ill patients with carbapenem-resistant Acinetobacter baumannii bacteraemia. Methods: An observational cohort study was carried out. Targeted therapy consisted of monotherapy with colistin (9 million UI/day) or combined therapy with colistin and tigecycline (100 g/day). The primary outcome was 30-day crude mortality. The association between combined targeted therapy and mortality was controlled for empirical therapy with colistin, propensity score of combined therapy and other potential confounding variables in a multivariate Cox regression analysis. Results: A total of 118 cases were analysed. Seventy-six patients (64%) received monotherapy and 42 patients (36%) received combined therapy. The source of bacteraemia was primary in 18% (21/118) of the patients, ventilator-associated pneumonia in 64% (76/118) and other sources in 14% (16/118). The 30-day crude mortality rate was 62% (42/76) for monotherapy and 57% (24/42) for combined therapy. The variables associated with 30-day crude mortality were: Charlson index (hazard ratio (HR) 1.16, 95% CI 1.02–1.32; p 0.028), empirical therapy with colistin (HR 2.25, 95% CI 1.33–3.80; p 0.003) and renal dysfunction before treatment (HR 1.91, 95% CI 1.01–3.61; p 0.045). Combined targeted therapy was not associated with lower adjusted 30-day crude mortality (adjusted HR 1.29, 95% CI 0.64–2.58; p 0.494). Conclusions: Combined targeted therapy with high-dose colistin and standard dose tigecycline was not associated with lower crude mortality of bacteraemia due to carbapenem-resistant A. baumannii in critically ill patients. Trial registration: Registered inClinicalTrials.gov . Identifier:NCT02573064 .